Реалізація альтернативних підходів для оцінки конуретноспроможності будівельних організацій - Медяник, О. І. (Ways to Improve Construction Efficiency, 2013)
Suggested alternative approaches to traditional methods of assessing the competitiveness of construction companies, which, unlike traditional approaches, taking into account modern requirements to the operating system as the leading contractor level implementation of construction projects. The new structure parameters and their universal measurement technique provides a reliable assessment of the competitiveness of construction companies performing their capacity for effective implementation of construction projects - as a basis for participation of financial and credit institution or investment firm investing in construction.